PENGARUH LATIHAN FOOTWORK BERBASIS TEKNOLOGI TERHADAP KETERAMPILAN TEKNIK DASAR BERMAIN BULUTANGKISCLUB PB. LYANSA 2020 - Lalu Sapta Wijaya Kusuma; Jamaludin Jamaludin (Universitas Pendidikan Mandalika, 2020)
One form of exercise that is most often applied in badminton training is shadow movement, this exercise aims to simulate badminton to do footwork properly and correctly. However, this form of training is quite classic in the badminton world, so it is necessary to have a special formula and media that can provide motivation and new enthusiasm when athletes practice. So in this case the researcher tries to apply technology-based exercises as a substitute for shadow movement or footwork exercises. the tool is a light module with a remote control that lights up as a marker for the direction of movement that the athlete must do. Meanwhile, the objective of this research is to determine whether or not technology-based footwork exercises are effective in improving the basic techniques of playing badminton. This type of research is an experiment by applying a pretest and posttest to the subjects studied in the form of a pre-test before and a final test in the form of a PB badminton playing skills test. Lyansa. The data analysis technique used is a prerequisite analysis test, namely normality (Shapiro-Wilk) and homogeneity (one way ANOVA), while to determine the difference in effect, a paired sample t-test is used with the help of SPSS version 17.0. The results of this study reveal that technology-based footwork training has more effect on lob accuracy than smash accuracy, with differences in the t-count value of Y1 (lob) = 18.71 and Y2 (smash) = 7.18. This difference was obtained because all athletes were never given a technical skill test during training, the test was only limited to physical ability. The ability to lob is more influential because most athletes at the beginning of training are trained more in the long ball technique and most athletes depart from the single type before being taught the double technique